Bimetallic NiCo Nanoparticles Embedded in Organic Group Functionalized Mesoporous Silica for Efficient Hydrogen Production from Ammonia Borane Hydrolysis - Juti Rani Deka; Diganta Saikia; Ning-Fang Lu; Chieh-Yu Chen; Hsien-Ming Kao; Yung-Chin Yang (Nanomaterials)
In this study, bimetallic NiCo nanoparticles (NPs) were encapsulated within the mesopores of carboxylic acid functionalized mesoporous silica (CMS) through the chemical reduction approach. Both NaBH4 and NH3BH3 were used as reducing agents to reduce the metal ions simultaneously. The resulting composite was used as a catalyst for hydrolysis of ammonia borane (NH3BH3, AB) to produce H2. The bimetallic NiCo NPs supported on carboxylic group functionalized mesoporous silica, referred to as NixCo100−x@CMS, exhibited significantly higher catalytic activity for AB hydrolysis compared to their monometallic counterparts. The remarkable activity of NixCo100−x@CMS could be ascribed to the synergistic contributions of Ni and Co, redox reaction during the hydrolysis, and the fine-tuned electronic structure. The catalytic performance of the NixCo100−x@CMS nanocatalyst was observed to be dependent on the composition of Ni and Co. Among all the compositions investigated, Ni40Co60@CMS demonstrated the highest catalytic activity, with a turn over frequency (TOF) of 18.95 molH2min−1molcatalyst−1 and H2 production rate of 8.0 L min−1g−1. The activity of Ni40Co60@CMS was approximately three times greater than that of Ni@CMS and about two times that of Co@CMS. The superior activity of Ni40Co60@CMS was attributed to its finely-tuned electronic structure, resulting from the electron transfer of Ni to Co. Furthermore, the nanocatalyst exhibited excellent durability, as the carboxylate group in the support provided a strong metal–support interaction, securely anchoring the NPs within the mesopores, preventing both agglomeration and leakage.